Legal Protection of Biological Children’s Inheritance Rights under Stepmother Control of Estate Property: An Empirical Study in Panyabungan Tonga Village - Jamilah Rizka; Mhd. Yadi Harahap; Nurcahaya (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
The realization of inheritance rights under Islamic law frequently encounters practical challenges despite the existence of comprehensive normative regulations. This study examines the legal protection of the inheritance rights of biological children in cases where estate property remains under the de facto control of a surviving stepmother. Employing an empirical juridical approach that integrates Islamic legal and socio-legal perspectives, the research was conducted in Panyabungan Tonga Village, Mandailing Natal Regency. Data were collected through interviews, documentation, and library research and analyzed qualitatively. The findings reveal that, following the decedent's death in 2018, the estate remained under the exclusive control of the surviving spouse without any legal separation between marital property and inheritance assets. This situation prevented the effective realization of the inheritance rights of the biological children from the first marriage. The study further identifies several contributing factors, including limited legal literacy, ineffective family deliberation, the absence of mediation by customary and religious leaders, and unequal access to information regarding the estate. These findings demonstrate a significant gap between the normative protection provided by Islamic inheritance law and the Indonesian Compilation of Islamic Law and its implementation in social practice. The study concludes that effective protection of inheritance rights requires not only clear legal norms but also transparent estate administration, strengthened legal awareness, and effective family-based dispute resolution mechanisms.